A Novel Biochemical Study of Anti-Dermal Fibroblast Replicative Senescence Potential of Panax Notoginseng Oligosaccharides - Zhai, Lu; Xu, Xiaohao; Liu, Jiangzeng; Jing, Chenxu; Yang, Xinzhao; Zhao, Daqing; Jiang, Rui; Sun, Li-Wei (Frontiers in Pharmacology, 2021)
Dermal fibroblast replicative senescence that often occurs in aging skin is characterized by loss of cell proliferative capacity, cell cycle arrest, decreased cell elongation, and decreased synthesis of dermal extracellular matrix (ECM) components. Although Panax notoginseng is known for its effectiveness in alleviating many age-related degenerative diseases, few studies have evaluated P. notoginseng components for efficacy or mechanisms of action in delaying cell replicative senescence. In this study, P. notoginseng oligosaccharides (PNO) were isolated using a stepwise purification procedure involving water extraction and alcohol precipitation followed by DEAE Sepharose Fast Flow column chromatography, preparative high performance liquid chromatography, and size-exclusion chromatography. Monosaccharides detected in PNO constituents included mannose, galactose, and sorbitose in relative molar proportions of 14.2:12.3:1, respectively, aligning with PNO absorption spectrum results resembling typical known spectra for sugars. In vitro, PNO treatment of replicative senescent NIH-3T3 fibroblasts significantly promoted cell vitality, inhibited SA-β-galactosidase (SA-β-Gal) activity, and reduced p16 and p21 protein-level expression. Moreover, PNO treatment of senescent fibroblasts led to a lower proportion of G1 phase cells and higher proportion of S phase cells, while also inducing aging NIH-3T3 cells to migrate and synthesize CoL-I. Mechanistically, PNO treatment up-regulated expression of proliferating cell nuclear antigen (PCNA), cyclin E, cyclin D1, and cyclin-dependent kinase 4 (CDK4) proteins and promoted phosphorylation of MEK, p38, and ERK1/2 to trigger cell cycle progression. Additionally, PNO treatment also up-regulated protein-level expression of TGF-β1 and levels of p-Smad2/3, p-FAK, and p-Pax to trigger CoL-I synthesis and cell migration. Taken together, these findings demonstrate that oligosaccharides purified from P. notoginseng could reverse fibroblast replicative senescence by promoting fibroblast cell proliferation, migration, and CoL-I production.